Targeting key angiogenic pathways with a bispecific CrossMAb optimized for neovascular eye diseases. Issue 7 (22nd May 2017) - Regula, Jörg T; Lundh von Leithner, Peter; Foxton, Richard; Barathi, Veluchamy A; Gemmy Cheung, Chui Ming; Bo Tun, Sai Bo; Wey, Yeo Sia; Iwata, Daiju; Dostalek, Miroslav; Moelleken, Jörg; Stubenrauch, Kay G; Nogoceke, Everson; et al.
Abstract :